(untitled) (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
In the article, the author revealed the results of his own generalizing methodical approaches and agrotechnical requirements for Strip-Till, which are based on a seven-year production experiment based on modal agricultural enterprises of Mykolaiv, Kyiv, Cherkasy and Kirovohrad regions. Sowing of any agricultural crop should be carried out at the optimal time and under optimal conditions. Corn is sown at a soil temperature of at least 10 °C at the sowing depth. because the germination of corn seeds occurs at a soil temperatureof about 7-9 °С. Sowing in insufficiently warmed soil leads to an increase in the germination period. Also, during the early sowing period, plants are more susceptible to the effects of diseases and pests. Late sowing can lead to the fact that the phase of intensive plant growth falls into the hottest and driest period, as a result of which the yield will decrease. Many physiological characteristics of a plant are formed in the early stages of growth, so it is very important to provide conditions for good plant development in the early stages. The historical prerequisites for the emergence of the Strip-Till technology were the search for ways to accelerate the heating of the soil in the area of future sowing. The key to quickly warming up the strip is to clean it of the harvest residues and form a strip with a convex profile, which helps it to dry and warm up.